Testing the Augmented Reality Functional Suitability of Wood as Raw Materials for Typical Crafts of East Borneo - Muhammad Bambang Firdaus; Zainal Arifin; Ruri Widi Priatna (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2021)
Borneo wood which has good quality wood for building basic materials and other purposes, has been widely known and sold. There are more than 120 types of wood, some of them are from Kalimantan. Cempaka wood, Putat wood, Mentibu wood, Meranti wood, Merbabu wood, Ironwood, Teak wood, and Sengon wood are included in various types, both endemic and from Borneo. This research is a continuation of previous research that has been running on the initial development of AR Wood, Raw Materials for Typical Crafts of East Borneo. This research aims to test forestry applications for information or socialization of the classification and utilization of East Borneo typical wood. This research objective can be achieved by using Augmented Reality (AR) technology which can incorporate almost all levels of virtual object society into the real environment and also use Android mobile technology. Therefore, functional adequacy testing is needed, namely black box testing and usability to find out how much the system can meet the needs if it is used as a raw material for East Borneo handicrafts, where the results of black box testing are good in test results for six features and standards. When using wood as a raw material, tests are carried out. With good classification results, usability reached 71.6%.